2018
DOI: 10.18203/2394-6040.ijcmph20180748
|View full text |Cite
|
Sign up to set email alerts
|

A study on assessment of mass drug administration for elimination of lymphatic filariasis in Datia district, Madhya Pradesh

Abstract: Background: Currently 947 million people globally live in areas having endemic lymphatic filariasis and require preventive chemotherapy to stop the spread of infection. LF is transmitted by many mosquitoes particularly Culex and in some areas by Anopheles and Aedes too. This study was conducted to assess the programme implementation with respect to process and outcome indicators and to assess the reasons for non-compliance among population.Methods: We conducted a cross sectional study in Datia district, Madhya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…12 In a similar study conducted in Madhya Pradesh Amarnath G observed coverage rate of 77.47% and compliance rate of 76.21%. 13 Muralidhar et al in their study found coverage rate 84.6% and compliance rate of 56.5%. 14 Abhay et al in their study revealed the overall coverage rate 79.7% and compliance rate 43.04%.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…12 In a similar study conducted in Madhya Pradesh Amarnath G observed coverage rate of 77.47% and compliance rate of 76.21%. 13 Muralidhar et al in their study found coverage rate 84.6% and compliance rate of 56.5%. 14 Abhay et al in their study revealed the overall coverage rate 79.7% and compliance rate 43.04%.…”
Section: Resultsmentioning
confidence: 87%
“…11.11% respondents had no faith on the drugs and 10.18% persons did not consumed the tablets due to some other reasons. 13 Karmakar PR observed that 30.57% persons did not consume. The most frequent cause was fear of side effect (36.84%) followed not having any clinical manifestation of filariasis (27.82%).…”
Section: Resultsmentioning
confidence: 99%
“…Only 17.5% had knowledge about transmission of disease, 46.66% had knowledge about availability of treatment and 55.83% had knowledge about MDA programme. 15 Kulkarni et al in their study found that only 49% of subjects had proper knowledge about the disease. 16…”
Section: Awareness About Lymphatic Filariasis and Mdamentioning
confidence: 93%
“…In various study conducted in different place in India by Anil, Lata et al, Naveenkumar, Kishore, Amarnath, Muralidhar et al and Nirgude et al also found low compliance rate than recommended level. [8][9][10][14][15][16][17] There is gender wise and age group wise differences in compliance rate in present study. A detailed inquiry into the matter might help us determine the cultural and social factors related age and gender which could have played a role in the compliance rate.…”
Section: Compliance Rate Of Mdamentioning
confidence: 95%
See 1 more Smart Citation